Development Progress and Industrialization Prospect of Hydrogen-Powered Aircraft - Song Weiwei; Yang Fengtian; Xiang Song; Han Chengye; Kang Guiwen; Fan Xinyue (中国工程科学, 2023)
The hydrogen energy serves as the best energy source for future aircraft owing to its efficiency, cleanness, and sustainability. In the context of widespread attention paid to aviation carbon reduction and the trend of low-carbon development of the aviation transportation industry, it is of great value to promote the development and application of hydrogen-powered aircraft. This study analyzes the development background of hydrogen-powered aircraft considering the carbon peaking and carbon neutrality goals for the aviation industry, and reviews the cutting-edge planning of hydrogen-powered aircraft in other countries as well as the latest progress in overall research and flight testing of hydrogen-powered aircraft in China. A detailed analysis is conducted on the key technology system for the development and application of hydrogen-powered aircraft, covering the overall design, liquid hydrogen storage tanks, hydrogen fuel cells, hydrogen-fueled turbine engines, hydrogen-fueled aviation internal combustion engines, safety and airworthiness technologies, and hydrogen refueling infrastructure. Focusing on the industrial application needs of future hydrogen powered aircraft, corresponding total cost of ownership (TCO) models are constructed for commuting/short-range hydrogen-powered aircraft. The calculation results indicate that the TCO of commuting/short-range hydrogen-powered aircraft will be on par with that of pure electric aircraft and fuel-powered aircraft around 2045. Further suggestions are proposed, including adhering to the synchronous development of multiple technological routes, prioritizing the development of power systems,conducting scientific and orderly research and development, and promoting the construction of airworthiness standards systems, thus to provide a basic reference for research on aviation technology innovation and high-quality development of the aviation transportation industry.